Condensation: A translation device for revealing complexity of knowledge practices in discourse, part 2—clausing and sequencing - Maton, Karl; Doran, Y. J. (Onomázein, 2017)
Complexity of knowledge practices is undertheorized in education research because knowledge is often conceived cognitively. Legitimation Code Theory conceptualizes this com-plexity in terms of ‘semantic density’, which explores how meanings are interrelated within practices. This concept is becoming widely enacted in research, a flexibility that raises the question of identifying ‘semantic density’ in specific objects of study. This is the second of two papers that offer a ‘translation device’ for identifying ‘epistemic-semantic density’ (whe-re condensed meanings are formal definitions or empirical descriptions) in English discourse. The first paper (this issue) provided tools for exploring how individual words reveals different strengths of epistemic-semantic density. Those concepts revealed different degrees of com-plexity of knowledge. This paper outlines tools for exploring how the ways actors combine words reveals ‘epistemological condensation’ or strengthening of epistemic-semantic densi-ty. It provides typologies for identifying different kinds of ‘clausing’ and ‘sequencing’ and des-cribes how these types manifest varying degrees of increasing complexity. These concepts reveal different kinds of knowledge-building. Two contrasting examples, from a secondary school History classroom and a scientific research article, are analysed to illustrate the in-sights into complexity offered by the tools outlined in both papers.